Development and clinical validation of a novel detection kit for α-thalassemia in southern Chinese - Ge, Yi-Yuan; Xie, Jun; Liao, Yu-Wei; Xie, Long-Xu; Yang, Li-Ye (Frontiers in Genetics, 2024)
Objective: This study aimed to develop and assess a novel reverse dot blot assay for the simultaneous detection of 10 types of α-thalassemia alleles in the Chinese population, including six common variants of -SEA , -α 3.7 , -α 4.2 , α CS , α QS , and α WS , and four rare variants of ααα anti-4.2 , ααα anti-3.7 , --FIL deletion and --THAI deletion.The novel thalassemia gene assay utilized a two-tier multiplex polymerase chain reaction amplification system and one round of hybridization. Genomic DNA samples were sourced from three hospitals in southern China. Each clinically validated DNA sample was re-evaluated using the new multiplex polymerase chain reaction/reverse dot blot assay Ⅲ (M-PCR/RDB Ⅲ).The study analyzed a total of 1148 unrelated participants, consisting of 810 thalassemia patients and 338 healthy control subjects. Valid hybridization results were obtained for 1147 samples, with one case (thalassemia carrier) being excluded from the study due to the poor quality of DNA. All 1147 samples, including those with α heterozygous thalassemia, α homozygous thalassemia, α compound heterozygous thalassemia, and control subjects were accurately genotyped, showing 100% concordance with the reference assays.The novel M-PCR/RDB Ⅲ assay proved to be simple, rapid, and precise, indicating its potential for genetic screening and clinical diagnosis of both common and rare α-thalassemia variants in Chinese populations.